Diabetes and Obesity as Independent Risk Factors for Osteoporosis in Postmenopausal Women: A Population Study. (September 2014) - Neglia, C.; Argentiero, A.; Chitano, G.; Agnello, N.; Giolli, L.; Di Tanna, G.; Paladini, D.; Amati, A.; Marsico, A.; Caiaffa, V.; Conte, P.; La Selva, G.; et al.
We aimed to analyze bone mineralization and the effect of different risk factors for osteoporosis in postmenopausal women. We studied 2, 756 postmenopausal subjects out of ≥10, 000 records from the ROIS registry in the frame of the PROF Project, a population study carried out in Salento (Taranto, Brindisi, Lecce) from 2009 to 2012. All subjects were assessed by phalangeal Quantitative Ultrasound (QUS) to evaluate their bone mineralization (assessed by Amplitude Dependent Speed of Sound, AD-SoS) and the association between demineralization and the presence of other conditions or risk factors. Mean age was 64±9.5 years and mean BMI was 28.7±3.5 Kg/m 2 . Pearson correlation analyses revealed a negative association between bone mineralization (AD-SoS) and BMI (P<0.001). By using multivariate logistic regression analysis, we observed significant values of Odds Ratios of osteoporosis (adjusted for age, physical activity and the use of drugs known to increase the risk of fractures) in subjects with diabetes and obesity: 1.39 (CI: 1, 05–1, 83) and 1.46 (CI: 1.20–1.78), respectively. A statistically significant linear trend of higher Odds Ratios of osteoporosis was found for increasing values of BMI. The percent change in the odds of vertebral fractures per single SD decrease of AD-SoS was 47% (P<0.001). Diabetes and obesity in postmenopausal women are likely to represent independent risk factors for osteoporosis. Phalangeal QUS showed a good power of predictivity in identifying subjects with vertebral fractures.